Relapse and Clinical Characteristics of Patients with Bipolar Disorders in Central Ethiopia: A Cross-Sectional Study. (28th September 2020) - Belete, Habte; Ali, Tilahun; Legas, Getasew
Abstract : Background . Bipolar disorder is a severe mental illness and has huge morbidity and mortality. Relapse is a challenging treatment failure in patients with mental illness, especially in patients with bipolar which causes high economic and social burdens. In the mental health delivery system, relapse is common and can be defined as becoming ill again after apparent recovery and a worsening condition of psychiatric patients. Due to psychiatric patients that may stop medication on their own in contrary to the advice of mental health professionals, relapse of mood episodes, delayed remission, and residual symptoms usually leads to hospitalization, increased suicide risk, and/or impede psychosocial recover. Therefore, understanding the nature of relapse in patients in low-income countries helps to prevent recurrence and related health care expenses. Objective . The objective of this study was to assess the prevalence and factors associated with relapse among patients with bipolar disorders in central Ethiopia. Method . Facility-based cross-sectional study was conducted from May to June 2015 at Amanuel Mental Specialized Hospital. Relapse was calculated among 400 samples of people with bipolar disorder, and systematic random sampling was used to select the study participants. Oslo's social support scale and ASSIST were used to identify factors with relapse, and a binary and multivariable logistic regression analysis model was performed to control the confounding factors. Odds ratios (OR) with the corresponding 95% confidence interval (95% CI) were determined to evaluate the strength of association. Results . The prevalence of relapse was 71% among patients with bipolar disorder. The longer morbidity (longer than 5 years) had a higher risk of relapse [adjusted   odd   ratio   AOR = 3.91, 95% confidence interval (CI): 2.44 to 6.27], while good medication adherence found to be a protective factor for relapse [AOR = 0.39, 95% CI: 0.22 to 0.72]. Conclusion . The prevalence of relapse was found pretty high among patients with bipolar disorders (71%). Working on treatment adherence and controlling the psychopathology is important to prevent relapse among bipolar patients.